Conditions influencing performance among young badminton players - Manaf, F.; Roy, J. (ISN-Bulletin, 2009)
The present study explored the different conditions that influenced performance (CIP) among young badminton players (n=18). Fifteen conditions (14 listed by Schubert) were ranked individually by the players with rank 1 as most influencing and rank 15 as least influencing. The 15th condition was left open to allow athletes to add their personal views. Percentage of athletes who assigned ranks up to first seven numbers were calculated, to demonstrate, the impact of the respective conditions. Content Overlap between the athletes were found out to examine the similarities in the subjective experiences of CIP. Moderate to high content overlap between most pair the athletes revealed, the similarities in the conditions influencing performance. The identified conditions call to design psychological interventions to deal with specific conditions.